2009
DOI: 10.1007/bf03218879
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of surface energy of BPDA-BAPP polyimide

Abstract: The surface properties (water sorption and repellency, adhesion) are closely related to the surface tension of polymer solids. The critical surface tension (γ c ) and surface tension (γ s ) of a polymer solid were estimated by the contact angle method by our quantitative imaging system. BPDA (3,3',4,4'-biphenyl tetracarboxylic dianhydride)-BAPP (1,3-Bis(4-aminophenoxy) propane) polyimide was successfully synthesized. The γ c values were analyzed by a Zisman plot, a Young-Dupré-Good-Girifalco plot, and a log (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Russell and his colleagues found that PIs (PMDA-ODA) show an ordered structure near the air surface, exhibiting a locally planar zigzag conformation and enhanced inter-chain packing than in the bulk . Kim calculated values of the surface energy (γ s ) and identified a dispersion component (γ d ), a polar component (γ p ), and a hydrogen bonding component (γ h ), yielding values of 40.31, 30.79, 9.32, and 0.20 mN/m, respectively . Using different approaches, Kim and Ban drew the same conclusion that the imide group is the most polar part in the PI chain.…”
Section: Introductionmentioning
confidence: 93%
“…Russell and his colleagues found that PIs (PMDA-ODA) show an ordered structure near the air surface, exhibiting a locally planar zigzag conformation and enhanced inter-chain packing than in the bulk . Kim calculated values of the surface energy (γ s ) and identified a dispersion component (γ d ), a polar component (γ p ), and a hydrogen bonding component (γ h ), yielding values of 40.31, 30.79, 9.32, and 0.20 mN/m, respectively . Using different approaches, Kim and Ban drew the same conclusion that the imide group is the most polar part in the PI chain.…”
Section: Introductionmentioning
confidence: 93%
“…To overwhelm these problems, incorporation of bulky pendent groups and aliphatic units 14,15 and the disruption of their symmetry have been suggested. However, as is well known, introduction of some groups, such as flexible ether and acyclic linkages, to the PI backbones will sacrifice their some advantageous properties, such as thermal stability and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] PIs are particularly important for electronic applications such as integrated circuit (IC) chips and semiconductor devices. In these applications, low-dielectric constant (low-k) materials are important in solving problems such as the resistance capacitance time delay, cross-talks, and power dissipation.…”
Section: Introductionmentioning
confidence: 99%